2022
DOI: 10.1002/biot.202200147
|View full text |Cite
|
Sign up to set email alerts
|

Apilimod enhances specific productivity in recombinant CHO cells through cell cycle arrest and mediation of autophagy

Abstract: Chinese hamster ovary (CHO) cells are expected to acquire the ability to produce higher recombinant therapeutic protein levels using various strategies. Genetic engineering targeting the cell cycle and autophagy pathways in the regulation of cell death in CHO cell cultures has received attention for enhancing the production of therapeutic proteins. In this study, we examined the small-molecule compound apilimod, which was found to have a positive influence on recombinant protein expression in CHO cells. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Autophagy pathway has a wide range of physiological effects and is a highly conserved lysosomal-mediated degradation mechanism in eukaryotic cells. Our previous studies found that the small molecule compound apilimod-treated CHO cells significantly inhibited autophagy and increased the yield of RTPs (Lu et al 2023 ).…”
Section: Overcome Strategies To Rtp Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy pathway has a wide range of physiological effects and is a highly conserved lysosomal-mediated degradation mechanism in eukaryotic cells. Our previous studies found that the small molecule compound apilimod-treated CHO cells significantly inhibited autophagy and increased the yield of RTPs (Lu et al 2023 ).…”
Section: Overcome Strategies To Rtp Degradationmentioning
confidence: 99%
“…In our previous studies, some strategies have been committed to improve the expression of recombinant proteins in mammalian cells (Life Technologies, #A11557-01), and screen the efficient expression vector elements (Li et al 2022a;Wang and Guo 2020;Wang et al 2023;Yang et al 2022), construct the cell line for enhancing transgenic expression and long-term stability (Jia et al 2018) and optimize serum-free cell medium (Li et al 2022b;Xu et al 2023) and other new optimization strategies in cell culture were also explored (Lu et al 2023;Yang et al 2022). With the increasing demands for RTPs, more attentions should be paid to the quality attributes of RTPs besides increasing the yields.…”
Section: Degradation Of Rtpsmentioning
confidence: 99%
“…[ 4–6 ] Therefore, to improve the transgene expression levels and stability, the use of genetic and cellular engineering methods to construct highly efficient homogeneous CHO cell lines is of great importance. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therefore, to improve the transgene expression levels and stability, the use of genetic and cellular engineering methods to construct highly efficient homogeneous CHO cell lines is of great importance. [7][8][9] Previous studies reported that the instability of recombinant protein expression in CHO cells is closely linked to epigenetic regulation. [10][11][12] For example, inhibition of DNA methylation can partially restore the specific productivity of recombinant CHO cells.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high-yield production systems, innovative approaches are needed to overcome some of the disadvantages of CHO, such as low cell productivity, restricted growth, unstable expression, and high production costs [ 8 , 9 ]. To satisfy the growing market requirement of biopharmaceuticals, the approaches such as gene modification, process optimization, expression vector and cell line modification are necessary to enable higher production capacity, higher product quality, and lower production costs [ [10] , [11] , [12] ]. Among of them, the modification of expression vector is a positive method to improve the yield of recombinant proteins, and expression vector cassette engineering and using chromatin-modifying elements can enhance the production level and stability of genes of interest (GOI) [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%